Basic Concepts of Tarbiyah Ta'lim and Ta'dib Education - Muhammad Yahya Azzam; Hafidz; Miftahul Huda Irfansyah; Suci adelia Pratiwi; Muhammad Yazid Ilhami; Sumayyah; Muhammad Dzaky Hilmi (Bulletin of Islamic Research, 2025)
This article examines the basic concept of Islamic education consisting of tarbiyah, ta'lim, and ta'dib. These three concepts are the most important foundation for the development of human resources who are knowledgeable, noble, and civilized in accordance with Islamic values. Tarbiya focuses on developing its overall physical, mental and spiritual potential. Ta'lim focuses on the systematic transfer of knowledge to improve understanding and skills. On the other hand, Ta'dib emphasizes moral and ethical education to develop civilized and responsible human beings. This study uses literature review techniques to analyze these concepts based on relevant literature. This analysis shows that the integration of tarbiyah, ta'lim, and tahdib can provide a comprehensive Islamic education framework to answer current challenges.